2014
DOI: 10.1142/s0219876213500850
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Characteristics of Bending, Buckling and Vibration of Nanobeams via Nonlocal Beam Theory

Abstract: In the present study, a nonlocal hyperbolic shear deformation theory is developed for the static flexure, buckling and free vibration analysis of nanobeams using the nonlocal differential constitutive relations of Eringen. The theory, which does not require shear correction factor, accounts for both small scale effects and hyperbolic variation of shear strains and consequently shear stresses through the thickness of the nanobeam. The equations of motion are derived from Hamilton's principle. Analytical solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…This result for the zigzag nanobeam is in accordance with the predictions of the nonlocal theory, [4,59] nonlocal shear deformation theory, [11] numerical meshless method, [15] and nonlocal shear deformation of the hyperbolic theory. [12] However, for the armchair nanobeam the amount of deflection is reduced and the nanobeam is harder compared to the local case which agrees with the predictions of the gradient [31] and Eringen-like models. [31] Thus, it may be concluded that a change in chirality can have a substantial effect on the hardness and softness of nanobeams.…”
Section: Simply Supported Nanobeams (S-s)supporting
confidence: 76%
See 2 more Smart Citations
“…This result for the zigzag nanobeam is in accordance with the predictions of the nonlocal theory, [4,59] nonlocal shear deformation theory, [11] numerical meshless method, [15] and nonlocal shear deformation of the hyperbolic theory. [12] However, for the armchair nanobeam the amount of deflection is reduced and the nanobeam is harder compared to the local case which agrees with the predictions of the gradient [31] and Eringen-like models. [31] Thus, it may be concluded that a change in chirality can have a substantial effect on the hardness and softness of nanobeams.…”
Section: Simply Supported Nanobeams (S-s)supporting
confidence: 76%
“…Table 3 illustrates for what values of length L, the scaling and chirality effects are more important. For this purpose, a normalized deflection is defined̂= 12 ∕ 0 . The classical normalized deflection is considered as the baseline and the percent variances of the deflection of zigzag and armchair Euler-Bernoulli nanobeams using Equations 60 and 61 are presented with respect to the baseline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 There are numerous studies related to the wave propagation, static, buckling and free linear and nonlinear vibration analysis of nanobeams and nanotubes based on di®erent beam theories. [8][9][10][11][12][13][14][15][16][17][18][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The theory of surface elasticity established by Gurtin et al 7 has been adopted to explain various size-dependent phenomena at the nanoscale, and the predictions¯t well with atomistic simulations and experimental measurements. [19][20][21] Wang and Feng 22 analyzed the surface e®ects on the axial buckling of nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, based on this new model, many studies have been conducted by developing and providing nonlocal beam models for the prediction of mechanical behaviors of homogenous and nonhomogeneous nanobeams. 31–52 Zhang et al. 53 carried out a free vibration study of nonlocal Timoshenko beams made of FGMs by employing symplectic method; the influences of various parameters were presented.…”
Section: Introductionmentioning
confidence: 99%